Kepuasan masyarakat terhadap pelayanan publik dalam mewujudkan good governance di Kecamatan Umbulharjo Kota Yogyakarta - Ahmad Izudin (Publisia: Jurnal Ilmu Administrasi Publik, 2019)
The sub-district office is a government institution and the arm of the state in providing services to the community. This service is also called public services that need assessment. With the spirit of bureaucratic decentralization that gave birth to regional autonomy, the assessment of public services needs to be measured through the Community Satisfaction Index (CSI). That way, this study formulates the CSI in the Umbullharjo sub-district Office, Yogyakarta City, which aims to determine the level of community satisfaction with the public services provided. For this reason, this study uses a survey method with quota sampling method, the instrument of which is a questionnaire as a data collection tool. Data collection methods were used by distributing questionnaires to 100 respondents—taken randomly with consecutive sampling. The calculation results of CSI refers to Ministrial Regulation for the Empeworment of State Apparaturs Bureaucratic of Reformation no. 16, 2014. The results showed that the CSI was 77.25, so the quality of public services was at the level of ‘B’ and the performance category was ‘Good’. This means that the performance of public services in the January-April 2017 period falls into a good category and the bureaucratic system runs at maximum.DOI: https://doi.org/10.26905/pjiap.v4i1.2199